Determination of Hypocentre and Seismic Velocity Structure in Guntur Volcano Using Seismic Data from 2010 to 2014 - Basuki, Ahmad; Nugraha, Andri Dian; Hidayati, Sri; Triastuty, Hetty (Geological Agency, 2019)
DOI: 10.17014/ijog.6.3.279-289Guntur Volcano was in a dormant state even though its seismicity had increased on April, 2013 and August, 2013. In this study, determination of hypocentre and seismic velocity structure was conducted using seismic data from 2010 to 2014 as recorded by a seismic station of the Centre for Volcanology and Geological Hazard Mitigation of Indonesia (CVGHM). Volcano-Tectonic (VT) earthquakes were identified and carefully picked for P-and S-wave arrival times. More than 600 events of VT earthquakes from 2010 - 2014 were located using maximum likelihood estimation algorithm. The initial 1-D seismic velocity was calculated using Velest method in order to get the initial velocity as the input for the tomographic inversion. The results show distribution of VT hypocentres were clustered in three regions, namely Guntur Volcano, Kamojang geothermal area, and Darajat geothermal area. At the Guntur Volcano region, the VT events were located mostly at the northern part of the crater with the depth of hypocentre ranges from 0 - 4 km. The distribution of the VT events made alignment from the southwest to the northeast with the depth of hypocentre mostly ranges from 0 - 2 km at Kamojang region. Meanwhile, at Darajat geothermal area, the VT events were located at the depth of 0 - 2 km and made alignment from the southeast to the northwest. The low velocity zone associated with hot material or fluids was located at the depth of 5 km beneath the Guntur Crater. The location of VT earthquakes at the depth of 0 - 4 km beneath Guntur Crater was coincided with the area with high Vp and Vs anomalies. The low velocity zones were also found at Kamojang Crater and Cipanas hotspring area. It was predicted that the low velocity zone at the Kamojang Crater was related to a high temperature of the vapour system, whereas the reservoir of water was preferred to be dominated at the Cipanas hotspring.